Розроблення елементів сенсорної техніки на основі структур кремній-на-ізоляторі та мікрокристалів кремнію, модифікованих домішками бору і нікелю - Ховерко, Юрій Миколайович (Національний університет "Львівська політехніка", 2016)
Дисертаційна робота присвячена вирішенню науково-прикладної проблеми створення елементів сенсорної техніки на основі структур кремній-на-ізоляторі, та мікрокристалів кремнію, легованих домішками бору і нікелю. Проведено комплексне дослідження електрофізичних властивостей структур кремній- на-ізоляторі та мікрокристалів кремнію у широкому інтервалі температур на постійному та змінному струмах, що є передумовою розроблення фізичних основ створення мікроелектронних сенсорів на базі полікристалічного та ниткоподібного кремнію і встановлено, що за кріогенних температур в околі температури рідкого гелію провідність змінюється стрибкоподібно по локалізованих домішкових рівнях. Обгрунтовано фізичні моделі, які описують деформаційно-стимульовані та спін-поляризаційні ефекти в мікрокристалах кремнію та КНІ-структурах, що лягло в основу розроблення нових підходів щодо створення елементів сенсорної техніки і дозволять прогнозувати необхідні параметри в процесі їх виготовлення. Запропоновано високочутливі сенсори деформації, температури, магнітного поля, що має важливе значення для сучасної кріоелектроніки, кріоенергетики, сенсорної мікро- та наноелектроніки, а також пристрої, що виготовлені за рахунок поєднання технологій отримання структур кремній-на-ізоляторі та мікрокристалів кремнію шляхом розроблення нових підходів та конструктивно-технологічних методів до формування функціональних властивостей приладів. Представлено чутливий елемент акселерометра, що дало можливість реалізувати як дискретний прилад, так і елемент зінтегрованих наноелектромеханічних систем зі структурою кремній-на-ізоляторі, який забезпечує контроль переміщення з точністю 200 нм. На основі комплексного використання мікрокристалів кремнію та структур кремній-на ізоляторі створено як дискретні елементи твердотільної електроніки (індуктивні, ємнісні елементи), так і комбіновані (коливальні контури), які реалізуються за суміщеними технологіями. Конструкція коливального контура передбачає комбінацію елементів, яка складається з ниткоподібного кристала кремнію із концентрацією легуючої домішки, що відповідає діелектричному боку переходу метал-діелектрик та полікристалічного кремнію в КНІ-структурах. Диссертация посвящена решению научно-прикладной проблемы создания элементов сенсорной техники на основе структур кремний-на-изоляторе и микрокристаллов кремния, легированных примесями бора и никеля. Проведено комплексное исследование электрофизических свойств структур кремний-на-изоляторе и микрокристаллов кремния в широком интервале температур на постоянном и переменном токах, что является предпосылкой разработки физических основ создания микроэлектронных сенсоров на базе поликристаллического и нитевидного кремния и установлено, что при криогенных температурах, возле температуры жидкого гелия проводимость, меняется скачкообразно по локализованным примесным уровням. Обоснованно физические модели, описывающие деформационно-стимулированные и спин-поляризационные эффекты в микрокристаллах кремния и КНИ-структурах, что легло в основу разработки новых подходов по созданию элементов сенсорной техники и позволят прогнозировать необходимые параметры в процессе их изготовления. Предложено высокочувствительные сенсоры деформации, температуры, магнитного поля, что имеет важное значение для современной криоэлектроники, криоэнергетики, сенсорной микро- и наноэлектроники, а также устройства, изготовленные за счет сочетания технологий получения структур кремний-на-изоляторе и микрокристаллов кремния путем разработки новых подходов и конструктивно-технологических методов к формированию функциональных свойств приборов. Представлено чувствительный элемент акселерометра, что позволило реализовать как дискретный прибор, так и элемент интегрированных наноэлектромеханических систем со структурой кремний-на-изоляторе, который обеспечивает контроль перемещения с точностью 200 нм. На основе комплексного использования микрокристаллов кремния и структур кремний-на изоляторе созданы как дискретные элементы твердотельной электроники (индуктивные, емкостные элементы), так и комбинированные (колебательные контуры), которые реализуются по совмещенным технологиям. Конструкция колебательного контура предусматривает комбинацию элементов, которая состоит из нитевидного кристалла кремния с концентрацией легирующей примеси, что соответствует диэлектрической стороне перехода металл-диэлектрик и поликристаллического кремния в КНИ-структурах. The thesis is devoted to the solution of scientific and applied problems of development of elements of sensing equipment on the basis of silicon-on-insulator structures and silicon microcrystals doped with boron and nickel impurities. A comprehensive study of electrical properties of silicon-on-insulator structures and silicon microcrystals in a wide temperature range at direct and alternating currents, which is a prerequisite for the development of physical foundations of microelectronic sensors based on polycrystalline and needle-like silicon was conducted, and it was established that at cryogenic temperatures in the vicinity of helium ones, the conductivity changes abruptly over localized impurity levels. The study of the properties of poly-silicon layers in SOI structures by impedance analysis method (AC measurements) allowed for determining the effect of material dispersion on its low-temperature conductivity and for separating and identifying the contributions of various microstructure elements in the sample conductivity. In both the DC and AC cases the Mott law hopping conductivity in non-recrystallized poly-Si samples has been confirmed at low temperatures (4.2 – 30 K). A capacitive type of Nyquist plot in turn supported this assumption. In laser-recrystallized poly-Si layers the charge carrier transport is limited by grain barriers and corresponds rather to percolation type of conduction, obeying the Shklovskii-Efros law The physical models were proposed to describe the strain-induced and spin polarization effects in silicon microcrystals and SOI structures, which formed the basis for the development of new approaches to the fabrication of elements of sensing equipment, and will allow to predict the required parameters in a manufacturing process. The results of low-temperature studies of magnetization of silicon nanocrystals doped with boron and nickel impurities showed that at liquid helium temperatures the crystal conductance changes abruptly due to localization of impurity levels. The magnetic properties of crystals, the concentration of which corresponds to a dielectric and metal side of metal-insulator transition, subject to the percolation laws of the formation of magnetic clusters, that in turn is important for the development of devices that can be used in spintronics. A highly sensitive strain, temperature, magnetic field sensors were proposed, which are important for modern cryoelectronics, cryoelectronic storage, sensor micro- and nanoelectronics, as well as for the devices made by combining the techniques of silicon-on-insulator structures and silicon microcrystals fabrication through the development of new approaches and structural and technological methods for the formation of functional properties of devices. The developed sensing element of accelerometer made it possible to implement as a discrete device or an element of integrated nanoelectromechanical system based on silicon-on-insulator structure, which provides the displacement with precision of 200 nm. Based on the multipurpose use of silicon microcrystals and silicon-on-insulator structures, the discrete solid state elements (inductive, capacitive elements) and combined elements (oscillatory circuits) implemented by positioning technologies were developed. The design of the oscillatory circuit provides a combination of elements consisting of silicon whisker with a dopant concentration corresponding to the dielectric side of metal-insulator transition and polycrystalline silicon in SOI structures.
Разработка элементов сенсорной техники на основе структур кремний-на-изоляторе и микрокристаллов кремния, модифицированных примесями бора и никеля
Development of elements of sensing equipment on the basis of silicon-on-insulator structures and silicon microcrystals, modified by boron and nickel impurities
Keywords: КНІ-структура; мікрокристал; кремній; деформація; кріогенні температури; високоенергетичне опромінення; магнітоопір; імпеданс; сенсор; КНИ-структура; микрокристалл; кремний; деформация; криогенные температуры; высокоэнергетическое облучения; магнитосопротивление; импеданс; сенсор; SOI-structure; microcrystal; silicon; strain; cryogenic temperatures; high-energy irradiation; magnetoresistance; impedance; sensor